Impact of Social Environment on Cognitive Abilities and Learning Outcomes in Bugis Bridal Make-Up Training - Meli Sabel; Soeprijanto Soeprijanto; Jenny Sista (PT. Anagata Sembagi Education, 2024)
Bugis bridal make-up is a traditional art form requiring specialized training to master its intricate techniques. Understanding the factors that influence learning outcomes in this field is crucial. Cognitive abilities and the social environment play significant roles in educational success, yet their impact on Bugis bridal make-up training remains underexplored. This study aims to examine the impact of the social environment on cognitive abilities and learning outcomes in Bugis bridal make-up training. A mixed-methods approach was utilized, involving quantitative surveys and qualitative interviews with 150 trainees from various training centers. Data were collected on participants' cognitive abilities, perceived social support, and learning outcomes. Statistical analyses were conducted to identify significant relationships, and thematic analysis was used to interpret qualitative data. The findings reveal a positive correlation between a supportive social environment and enhanced cognitive abilities, which in turn significantly improve learning outcomes in Bugis bridal make-up training. Trainees who reported higher levels of social support demonstrated better cognitive performance and achieved higher proficiency in make-up skills